Sectoral Analysis of The Economic Potential Development to Support Government Policy in Banjar District, South of Kalimantan - Merilu Ripner; Andi Tenri Sompa; Ahmad Yunani (International Journal of Politic, Public Policy and Environmental Issues, 2021)
The COVID-19 pandemic situation, leadership succession, and changes in the RPJMD certainly provide challenges and opportunities for local governments to maintain the existence and sustainability of economic growth. Short-term solutions are needed to help leading sectors continue to have an impact on economic growth. Identification and specific strategies in determining leading sectors are essential in a pandemic condition where the economic situation is uncertain. The purpose of this study was to determine the sector that has the potential to be a leading, competitive, and fast-growing sector in regional development in Banjar Regency during and after the Covid 19 pandemic. This study used research methods and designs starting from the Quantitative-Qualitative Research Methods. Based on the study results, the determination of the leading sector based on the calculation ranking of LQ, Shift Share, and I - O uses slices and sees the most considerable contribution to GRDP and the workforce absorbed in that sector. 3 The main sectors that excel are Wholesale and Retail Trade, Repair of Cars and Motorcycles; Provision of Accommodation and Food and Drink; Agriculture, Forestry and Fisheries. Based on the results of the AHP analysis of the respondents, it shows that the priority policy criteria are prioritized on the development of the leading economic sector in Banjar Regency, with the priority being infrastructure development, the second being institutional improvement, while the investment aspect is the third priority. The aspect of market expansion becomes the fourth priority, and the fifth and sixth priorities are the development of Special Economic Zones and aspects of sustainability. Meanwhile, the farmer or the community, the actor or party that has the most crucial role in developing the leading sector in Banjar Regency based on the respondent's choice. The Government is considered the second most crucial actor in implementing leading sector activities due to the lack of basic facilities supporting economic and trade activities. Furthermore, Social Organizations and Private Parties or Investors as other important actors in developing leading sectors in Banjar Regency